Cartogramas quantitativos - recursos e restricoes - Sanchez, M. C.; Custodio, P. (My University, 1990)
This paper aims at illustrating the importance of the Thematic Map. Making For the Scientific Areas which are concerned with the issue of spatial representation of the quantified items. At first, the placement of the document definitions such as maps, charts, and cartograms is carried out in order to deal, next, with the fundamental issue for the elaboration of choropleths cartograms what are the determination of the class intervals. A number of criteria have been used for the elaboration of the six choropleths cartograms being making it evident the importance of the criterion to be used in the choice of the class intervals. By considering that there is not a better criterion than another one but, instead, one more adequate for each situation, there becomes evident the need for knowing the resources as well as the restrictions of the various criteria of choice of the class intervals thus avoiding making bad choices or biased ones. -English summary
Quantitative cartograms: resources and restrictions
Keywords: cartogram; class interval; mapping; thematic map making